2008
DOI: 10.1016/j.ydbio.2008.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Wnt6 signaling regulates heart muscle development during organogenesis

Abstract: Mesodermal tissue with heart forming potential (cardiogenic mesoderm) is induced during gastrulation. This cardiogenic mesoderm later differentiates into heart muscle tissue (myocardium) and non-muscular heart tissue. Inhibition of Wnt/β-catenin signaling is known to be required early for induction of cardiogenic mesoderm; however, the identity of the inhibiting Wnt signal itself is still elusive. We have identified Wnt6 in Xenopus as an endogenous Wnt signal, which is expressed in tissues close to and later i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 35 publications
(41 reference statements)
2
44
0
Order By: Relevance
“…86 A natural in vivo ligand for this repressive effect of Wnt/␤-catenin signaling on cardiogenesis could be Wnt6. 87 Overexpression of Wnt6 in transgenic Xenopus embryos using a heat shock-inducible promotor during stages of terminal differentiation resulted in decreased cardiac structures. In contrast, depleting Wnt6 by use of antisense morpholino oligonucleotides resulted in enlarged cardiac structures.…”
Section: Wnt Signaling During Terminal Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…86 A natural in vivo ligand for this repressive effect of Wnt/␤-catenin signaling on cardiogenesis could be Wnt6. 87 Overexpression of Wnt6 in transgenic Xenopus embryos using a heat shock-inducible promotor during stages of terminal differentiation resulted in decreased cardiac structures. In contrast, depleting Wnt6 by use of antisense morpholino oligonucleotides resulted in enlarged cardiac structures.…”
Section: Wnt Signaling During Terminal Differentiationmentioning
confidence: 99%
“…32,[61][62][63][64]66 Linear heart tube formation ␤-catenin required for cell-cell contact Supports cell adhesion 59,77,88,89,92,93 ; required for morphogenesis 87,89,95 OFT morphogenesis Required for septation (CNCCs) [103][104][105] Required for cytoskeleton formation and cell-cell interactions 77,[106][107][108][109][110][111] Cardiac looping Required (zebrafish) 98 Not known…”
Section: Disclosuresmentioning
confidence: 99%
“…Understanding the function of the WNT pathway for CP specification has been more challenging, as canonical WNT signaling both promotes and restrains CP specification (Kwon et al, 2007;Lavery et al, 2008;Naito et al, 2006;Paige et al, 2010;Tzahor, 2007;Ueno et al, 2007). During gastrulation, WNT activity induces ventrolateral mesoderm to establish the precardiac territory.…”
Section: Introductionmentioning
confidence: 99%
“…Studies with ES cells indicated that canonical WNTs could have a positive influence of cardiac tissue formation [23][24][25][26][27][28]. Recent investigations in the whole embryo suggested that timing during development may determine whether cardiac differentiation is stimulated or suppressed by canonical WNTs, and have prompted a modified hypothesis that these molecules have a biphasic influence on heart development [12,13,16,26,30]. Thus, it has been proposed that exposure to canonical WNT signals before gastrulation is required for cardiac induction and/or expansion of cardiac progenitors, whereas once gastrulation begins, suppression of these same signals is necessary to allow cardiac differentiation to continue.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, WNT regulation of cardiogenesis may not be so clear cut, as investigations with embryonic stem cells have indicated that both canonical and noncanonical WNTs promote cardiac differentiation [23][24][25][26][27][28]. Recent studies suggested that canonical WNT regulation of cardiac differentiation may be phasic, either promoting or inhibiting cardiogenesis, depending on the stage in development [12,13,16,26,29,30].…”
mentioning
confidence: 99%